2016
DOI: 10.1007/s00394-016-1345-3
|View full text |Cite
|
Sign up to set email alerts
|

Controversies about sugars: results from systematic reviews and meta-analyses on obesity, cardiometabolic disease and diabetes

Abstract: Fructose-containing sugars are a focus of attention as a public health target for their putative role in obesity and cardiometabolic disease including diabetes. The fructose moiety is singled out to be the primary driver for the harms of sugars due to its unique endocrine signal and pathophysiological role. However, this is only supported by ecological studies, animal models of overfeeding and select human intervention studies with supraphysiological doses or lack of control for energy. The highest level of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
157
1
16

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(176 citation statements)
references
References 139 publications
2
157
1
16
Order By: Relevance
“…HFCS is used to sweeten products like SSBs (eg, soda, sports drinks, fruit drinks) . Due to significant, global consumption of SSB products, HFCS's relationship to T2D risk has repeatedly been studied by researchers with some still questioning if HFCS actually increases an individual's risk of developing T2D . Results from a systematic review and meta‐analysis by Khan and Sievenpiper did not find evidence to support that fructose contributes to an increase in T2D risk and reported that no controlled trials exist to support the association.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HFCS is used to sweeten products like SSBs (eg, soda, sports drinks, fruit drinks) . Due to significant, global consumption of SSB products, HFCS's relationship to T2D risk has repeatedly been studied by researchers with some still questioning if HFCS actually increases an individual's risk of developing T2D . Results from a systematic review and meta‐analysis by Khan and Sievenpiper did not find evidence to support that fructose contributes to an increase in T2D risk and reported that no controlled trials exist to support the association.…”
Section: Resultsmentioning
confidence: 99%
“…Because added sugar is found in a variety of dietary foods and beverages, terms were often interchanged to describe added sugar or components of added sugar (eg, glucose and fructose). These examples include words like sugar, sucrose, free sugars, dietary sugars, nutritive sweeteners, sugar‐sweetened beverages (SSB), high glycemic carbohydrates, high‐fructose corn syrup (HFCS), fructose, and fructose‐containing sugars . Several publications studied SSB consumption which was not always portrayed as an exclusive “added sugar product”, but rather as a product containing HFCS .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugar-sweetened beverages are associated with an increased risk of DM [22], but sugar does not trigger DM [23]. The pathological condition of GDM is attributable to reduced insulin secretion secondary to reduced pancreatic beta cell function during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Four of these reviews detailed mechanisms by which dietary fructose may have direct deleterious effects on human health . The other four concluded that dietary fructose has no detrimental effects on health except those related to an increased chance of excessive energy intake and weight gain . This latter conclusion is contradicted by the work of Schwarz et al .…”
mentioning
confidence: 99%